Junqueira’s Basic Histology : Text & Atlas (15th ed.), 2018 - of journal "Morphologia", Editorial office (Морфологія / Morphologia / Morfologìâ, 2019)
With this 15th edition, Junqueira’s Basic Histology continues as a major source of concise but comprehensive information on the structure and function of human tissues. For over 45 years, this educational resource has met the needs of students in an orderly and concise presentation of cell biology and histology, combining material with biochemistry, immunology, endocrinology and physiology and providing an excellent basis for further research in pathology.